Editorial Vol.5(1) - Sharma, Deewakar (Nepalese Heart Journal, 2008)
This year cardiac society has become 10 years old. These ten years have been the Period of turmoil, conflict, debate and economic problems for the country, But ironically, the field of cardiology has made lot of progress in the country in these last ten years, Fortunately, it remained less affected by the political, social and economic problems of the country.